The Meaning of Education Through the Concept of Ta'lim in the Koran - Aisi Jumarni; Pathur Rahman; Halimatussadiyah (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2024)
The scholars agree that the science of Tafsir of the Koran is the oldest scientific discipline in the treasures of Islamic knowledge. This science has been inherited from the time of the Prophet Muhammad and developed until the modern era. The emergence of knowledge in understanding Allah's verses in His book is intended so that humans can understand and practice the things that are said in the Koran. The language of the Koran, which has high quality and is unmatched by humans or jinn, requires a complex understanding so that the goal of creating humans as caliphs on earth does not experience errors in carrying out their lives. This research uses a qualitative approach to gain an in-depth understanding of the concept of ta'lim in the Al-Qur'an. Text analysis methods and interpretive approaches are used to explore hidden meanings in verses of the Qur'an, especially those that review educational terminology as ta'lim. Therefore, every Muslim is given the authority always to study, reflect, and practice its meanings. Furthermore, speaking about education in ta'lim terms, Islamic educational institutions are expected to be able to develop educational systems or methods that are by Islamic principles based on the Koran and As-Sunnah. By upholding these two heritages, namely the Koran and As-Sunnah, it is hoped that efforts to give birth to a superior generation who are promised God's help and blessings will be realised.